Recapitulation of developmental mechanisms to revascularise the ischemic heart - Dube, K; Thomas, T; Munshaw, S; Rohling, M; Riley, P; Smart, N (American Society for Clinical Investigation, 2017)
Restoring blood flow after myocardial infarction (MI) is essential for survival of existing and newly regenerated tissue. Endogenous vascular repair processes are deployed following injury, but are poorly understood. We sought to determine whether developmental mechanisms of coronary vessel formation are intrinsically reactivated in the adult mouse post-MI. Using pulse-chase genetic lineage tracing, we establish that de novo vessel formation constitutes a significant component of the neovascular response, with apparent cellular contributions from the endocardium and coronary sinus. The adult heart reverts to its former hypertrabeculated state and repeats the process of compaction, which may facilitate endocardium-derived neovascularisation. The capacity for angiogenic sprouting of the coronary sinus vein, the adult derivative of the sinus venosus, may also reflect its embryonic origin. The quiescent epicardium is reactivated and, while direct cellular contribution to new vessels is minimal, it supports the directional expansion of the neovessel network towards the infarcted myocardium. Thymosin β4, a peptide with roles in vascular development, was required for endocardial compaction, epicardial vessel expansion and smooth muscle cell recruitment. Insight into pathways that regulate endogenous vascular repair, drawing on comparisons with development, may reveal novel targets for therapeutically enhancing neovascularisation.